Influence of Storage Conditions on Stability of Phenolic Compounds and Antioxidant Activity Values in Nutraceutical Mixtures with Edible Flowers as New Dietary Supplements - Martina Mrázková; Daniela Sumczynski; Jana Orsavová (MDPI AG, 2023)
This paper investigates the effects of storage conditions on the stability of phenolics and their antioxidant activities in unique nutraceutical supplements containing non-traditional cereal flakes, edible flowers, fruits, nuts, and seeds. Significant total phenolic content (TPC) of 1170-2430 mg GAE/kg and total anthocyanin content (TAC) with the values of 322-663 mg C3G/kg were determined with the highest TPC content established in free phenolic fractions. The most notable declines in TPC (by 53%), TAC (by 62%), phenolics (e.g., glycosylated anthocyanins by 35-67%), and antioxidant activity (by 25% using DPPH) were established in the presence of sunlight at 23 °C followed by the storage at 40 °C. Quercetin, rutin, peonidin, pelargonidin, p-coumaric, ellagic, and p-hydroxybenzoic acids were identified as the least stable phenolics when exposed to sunlight. Furthermore, glycosylated forms of anthocyanins demonstrated a greater stability when compared with anthocyanidins. The mixtures considerably eliminated ABTS and DPPH radicals. In all samples, water-soluble substances showed a higher antioxidant activity than lipid-soluble substances with the main contributors in the following order: delphinidin-3-glucoside (r = +0.9839) > p-coumaric > gallic > sinapic > p-hydroxybenzoic acids > delphinidin > peonidin and malvidin (r = +0.6538). Gluten-free nutraceutical mixtures M3 (containing red rice and black quinoa flakes, red and blue cornflowers, blueberries, and barberries) and M4 (containing red and black rice flakes, rose, blue cornflower, blueberries, raspberries, and barberries) were evaluated as the least stable under all storage conditions although they showed considerable phenolic concentrations. Phenolic contents and antioxidant activity of the nutraceutical mixtures were the highest at 23 °C without the presence of sunlight with the most stable M1 nutraceutical mixture (containing oat and red wheat flakes, hibiscus, lavender, blueberries, raspberries, and barberries).